A qualitative study of primary care clinicians' views of treating childhood obesity - Atchinson Rebecca; Strong Mark; Walker Olivia; Saunders Joanna; Abbott Jo (BMC Family Practice, 2007)
Abstract Background The prevalence of childhood obesity is rising and the UK Government have stated a commitment to addressing obesity in general. One method has been to include indicators relating to obesity within the GP pay-for-performance Quality and Outcomes Framework (QOF) contract. This study aimed to explore general practitioners' and practice nurses' views in relation to their role in treating childhood obesity. Methods We interviewed eighteen practitioners (twelve GPs and six nurses) who worked in general practices contracting with Rotherham Primary Care Trust. Interviews were face to face and semi structured. The transcribed data were analysed using framework analysis. Results GPs and practice nurses felt that their role was to raise the issue of a child's weight, but that ultimately obesity was a social and family problem. Time constraint, lack of training and lack of resources were identified as important barriers to addressing childhood obesity. There was concern that the clinician-patient relationship could be adversely affected by discussing what was often seen as a sensitive topic. GPs and practice nurses felt ill-equipped to tackle childhood obesity given the lack of evidence for effective interventions, and were sceptical that providing diet and exercise advice would have any impact upon a child's weight. Conclusion GPs and practice nurses felt that their role in obesity management was centred upon raising the issue of a child's weight, and providing basic diet and exercise advice. Clinicians may find it difficult to make a significant impact on childhood obesity while the evidence base for effective management remains poor. Until the lack of effective interventions is addressed, implementing additional targets (for example through the QOF) may not be effective.